Уголовно - правовая охрана тайн в условиях современности [Articol] - Гырла, Лилия (Tipografia Artpoligraf, 2019)
This scientific research is dedicated to reconceptualization of the secret penal protection in accordance with the Criminal code of Republic of Moldova. During the general research of secrets there is shown that in Moldavian legislation doesn’t exist any penal norm which would be able to incriminate and punish the violation of professional secret regime, being provided by law only violation of personal inviolability by means of disclosure of personal secret. In such a situation the law is deficient and needs updates. In order to improve it, the author demonstrated the stringent necessity to introduce a legal definition of the professional secret in the content of the General part of the Criminal code. At the same time, in order to ensure the reasonableness of research the author has performed an analysis of modern doctrine in the sphere of Substantive Criminal Law. As a result, several conclusions have been formulated being designed to clarify the legal nature professional secrets and to ensure the standardized application of the penal norms.
CRIMINAL-LAW PROTECTION OF SECRETS IN MODERN CONDITIONS
Keywords: personal secret; secret professional